The role of primary cilia in congenital heart defect-associated neurological impairments - Sarić, Nemanja; Ishibashi, Nobuyuki (Frontiers in Genetics, 2024)
Congenital heart disease (CHD) has, despite significant improvements in patient survival, increasingly become associated with neurological deficits during infancy that persist into adulthood. These impairments afflict a wide range of behavioral domains including executive function, motor learning and coordination, social interaction, and language acquisition, reflecting alterations in multiple brain areas. In the past few decades, it has become clear that CHD is highly genetically heterogeneous, with large chromosomal aneuploidies and copy number variants (CNVs) as well as single nucleotide polymorphisms (SNPs) being implicated in CHD pathogenesis. Intriguingly, many of the identified loss-of-function genetic variants occur in genes important for primary cilia integrity and function, hinting at a key role for primary cilia in CHD. Here we review the current evidence for CHD primary cilia associated genetic variants, their independent functions during cardiac and brain development and their influence on behavior. We also highlight the role of environmental exposures in CHD, including stressors such as surgical factors and anesthesia, and how they might interact with ciliary genetic predispositions to determine the final neurodevelopmental outcome. The multifactorial nature of CHD and neurological impairments linked with it will, on one hand, likely necessitate therapeutic targeting of molecular pathways and neurobehavioral deficits shared by disparate forms of CHD. On the other hand, strategies for better CHD patient stratification based on genomic data, gestational and surgical history, and CHD complexity would allow for more precise therapeutic targeting of comorbid neurological deficits.